1994
DOI: 10.1093/bja/72.2.195
|View full text |Cite
|
Sign up to set email alerts
|

A survey of nasotracheal intubating skills among Advanced Trauma Life Support course graduates

Abstract: The American College of Surgeons' Advanced Trauma Life Support procedure teaches that blind nasotracheal intubation should be performed in the presence of a suspected or proven cervical spine injury in an unconscious but breathing patient who requires an artificial airway. We studied a group of non-anaesthetically trained graduates of the Advanced Trauma Life Support course and examined their skill in performing blind nasal intubations. Only six in 90 attempts were successful. We conclude that, in British hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 8 publications
(8 reference statements)
1
2
0
2
Order By: Relevance
“…The techniques of blind intubation [36,37] and fibre-optic guidance require more formal training. A study of nonanaesthetically trained graduates of the Advanced Trauma Life Support course asked to perform blind nasal intubation showed a high failure rate [55]. This review strengthens the view that there is no substitute for clinical experience in the performance of this technique.…”
Section: Trainingsupporting
confidence: 55%
“…The techniques of blind intubation [36,37] and fibre-optic guidance require more formal training. A study of nonanaesthetically trained graduates of the Advanced Trauma Life Support course asked to perform blind nasal intubation showed a high failure rate [55]. This review strengthens the view that there is no substitute for clinical experience in the performance of this technique.…”
Section: Trainingsupporting
confidence: 55%
“…Although all provide an excellent airway, their use must be tempered by the providers experience with the techniques and the ability to maintain cervical spine immobilization during the procedure. For example, nasotracheal intubation provides an excellent airway, but is difficult to perform and requires a spontaneously breathing patient, and is contraindicated in certain injury situations [33]. Several studies have shown that orotracheal intubation with manual in-line stabilization is an effective method of gaining an airway, even in the presence of cervical spine injury [34][35][36][37][38].…”
Section: Airways With Cervical Spine Immobilizationmentioning
confidence: 99%
“…Nasal intubation is probably not appropriate for the trauma victim and furthermore, a survey of ATLS trained personnel revealed a poor success rate for intubation via this route. 50 It is now clear that in experienced hands, oral intubation of the trachea is the preferred method, particularly for the trauma patient. 18 64 66 The view at laryngoscopy is also significantly improved if the cervical collar is removed 36 and if there are enough personnel available this should be done while the neck is stabilized manually.…”
Section: Tracheal Intubationmentioning
confidence: 99%